Implementation of Min-Max Stock Insert Components to Prevent Lost Opportunity Tooling Case Study: Automotive Component Company - Imansuri, Febriza; Hermawan, Yuda; Sumasto, Fredy; Pratama, Indra Rizki; Dendra, Feby Gusti; Imdam, Irma Agustiningsih (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Inadequate or delayed supply of raw materials or components needed for production can lead to line stoppages. Reducing the frequency and duration of line stoppages is crucial for maintaining efficiency and meeting production targets. It can happen due to logistics problemsThis research was conducted in the logistics department of an automotive component company. One of the causes is the procurement of tooling, which needs to be improved for production needs. The tooling factor is part of the logistics scope and is the highest factor causing lost opportunities and line stoppages. To minimize the impact of line production stoppages, manufacturers often implement strategies like implementing a minimum stock of insert components. The problem-solving methodology includes a five whys analysis, conducting a Pareto diagram, determining the service level of the stock level, and calculating the maximum-minimum stock level. Based on the result, 17 types of inserts must apply stock levels to avoid stock shortages.